Using Twitter to understand perspectives and experiences of dementia and caregiving at the beginning of the COVID-19 pandemic. (July 2022) - Bartmess, Marissa; Talbot, Catherine; O'Dwyer, Siobhan T.; Lopez, Ruth Palan; Rose, Karen M.; Anderson, Joel G.
The COVID-19 pandemic has placed a tremendous burden on all of society, particularly among vulnerable populations such as people living with dementia and their caregivers. Efforts to understand the impact of the COVID-19 pandemic on those living with dementia are crucial towards addressing needs during the pandemic and beyond. This qualitative descriptive study includes a thematic analysis of 6938 tweets from March 17–24, 2020, that included direct or indirect references to COVID-19 and at least one of the following terms/hashtags: Alzheimer, #Alzheimer, dementia, and #dementia. Five themes were identified: continuing care, finding support, preventing spread of COVID-19, maintaining human rights, and the impact of the pandemic on the daily lives of people living with dementia. People living with dementia and their families faced unique challenges related to caregiving, maintaining social connectedness while trying to follow public health guidelines, and navigating the convergence of COVID-19 and dementia-related stigma. Data from Twitter can be an effective means to understand the impacts of public health emergencies among those living with dementia and how to address their needs moving forward by highlighting gaps in practice, services, and research.